Inverse Strategies for Identifying the Parameters of Constitutive Laws of Metal Sheets. (20th September 2016) - Prates, P. A.; Pereira, A. F. G.; Sakharova, N. A.; Oliveira, M. C.; Fernandes, J. V.
Abstract : This article is a review regarding recently developed inverse strategies coupled with finite element simulations for the identification of the parameters of constitutive laws that describe the plastic behaviour of metal sheets. It highlights that the identification procedure is dictated by the loading conditions, the geometry of the sample, the type of experimental results selected for the analysis, the cost function, and optimization algorithm used. Also, the type of constitutive law (isotropic and/or kinematic hardening laws and/or anisotropic yield criterion), whose parameters are intended to be identified, affects the whole identification procedure.